The Power of Language in Changing a Community’s Story - Godfrey, Linda (Maine Policy Review, 2015)
To revive the community and reverse negative images of the town, community leaders in Eastport, Maine relied on the power of language. This article illustrates their efforts to inspire change by using words from well known leaders and replacing DE-words such as depressed and decline with RE-words such as rebound and renew.